Quantification of Que ac 1 and Standardization of Pollen Extract from Sawtooth Oak, the Most Important Cause of Spring Pollinosis in Korea - Jeong, Kyoung Yong; Lee, Jongsun; Park, Kyung Hee; Lee, Jae-Hyun; Park, Jung-Won (Allergy, asthma & immunology research, 2021)
KCI Citation Count: 0